Iran and Venezuela: From Peripheral Realism to Resilient Diplomacy (1999-2023) - Cardozo, Alejandro (2023)
This article aims to demonstrate that Tehran and Caracas have managed to circumvent the dynamics of the international system, and have developed alternative ways of surviving the liberal order through resilient diplomacy.. Which, according to the evidence we provide, surpasses the theory of peripheral realism, not as an epistemological improvement, but as empirical facts of the foreign policy of both. Iran and Venezuela have developed two revolutionary diplomatic phases that respond to two critical moments in their relations with the Liberal International System (LIS), a rebellious phase (Chávez- Ahmadinejad) and challenges where the  postulates of peripheral realism are met and later a resilient diplomacy (MaduroRaisi) that allows overcoming the LIS pressures and punishments.